Fighting an old disease with next-generation sequencing - Anzaan Dippenaar; Robin M Warren (eLife, 2015)
Whole genome sequencing has revealed that most cases of tuberculosis in a high-incidence setting in Malawi were caused by just one lineage of the bacterium responsible for the disease.